Implementation of Smart Patrol in the Management of the Lipan and Rakit Island Marine Protected Areas - Agus Rhismanda; Aan Saputra; Abdul Muis; Saptono Waspodo; Muhammad Haikal Abdurachman (Jurnal Biologi Tropis, 2023)
Smart Patrol application-based surveillance and monitoring activities are a form of patrol to communities that utilize conservation areas. This activity aims to determine the pattern of utilization and the level of community compliance with zoning in the Marine Conservation area of Lipan Island and Rakit Island. This research was carried out in January-December 2021 with a total patrol of 25 times / year, involving 3 Supervisory community groups (POKMASWAS): Kuda Laut, Karya Abadi and Lestari Bahari. The results of this study showed that there were 50 utilization points by 121 people from various villages: Labuhan Sangoro, Teluk Santong, Labuhan Aji, Labuhan Jambu, and Labuhan Kuris. In general, the fishing gear used is dominated by Gill Nets (28%) and Arrows (20%) with the composition of the catch being Reef fish (57%) and Small Pelagic fish (31%). Meanwhile, based on the level of fishermen's compliance in each zoning in the core zone, including the good category (76%), the utilization zone (97%) and the rehabilitation zone (98%) are in the excellent category